OPTIMIZATION OF SAT INTELKAM POLRES PATIS’S SKCK KELILING SERVICE TO IMPROVE PUBLIC SERVICE RESPONSIBILITY - RULLI JEREMY SIREGAR SIREGAR (Indonesian Journal of Police Studies, 2022)
OPTIMIZATION OF SAT INTELKAM POLRES PATIS’S SKCK KELILING SERVICE TO IMPROVE PUBLIC SERVICE RESPONSIBILITY Rulli Jeremy Andika Halomoan Siregar Akademi Kepolisian Semarang Semarang, Jawa Tengah, Indonesia, 50232 Email: jeremysiregar7500@gmail.com ABSTRACT In 2021, Indonesia also has not finished handling the Covid-19 pandemic since 2020 which has caused limited space for people to move due to the PPKM program. Polres Pati continue to strive to improve services to the community. Sat Intelkam Polres Pati provides a humane service innovation to the community in the form of a SKCK Keliling Service. However, in its implementation is still not optimal. From the report on the total number of SKCKs printed by the Polres Pati in October 2021, there were 1156 sheets, only 15 of which went through the SKCK Keliling service. Therefore, the objectives of this study were: 1) to determine the initial conditions of the Polres Pati’s SKCK Keliling service; and 2) explaining the efforts to optimize the Polres Pati’s SKCK Keliling service. This research is a qualitative research which refers to the development of an activity (developmental research). Data collection methods were carried out through observation, interviews and document studies. Primary data sources were obtained from interviews consisting of Kapolres Pati, Kasat Intelkam Polres Pati, KBO Satuan Intelkam Polres Pati, Kauryanmin Sat Intelkam Polres Pati and the SKCK applicant community. The validity of the data was tested by triangulation of sources and methods. Then, data analysis begins with data reduction, data presentation and drawing conclusions. The results of this study indicate that in planning the SKCK Keliling activities should be included in the activity plan (Rencana Kegiatan) of the Sat Intelkam Polres Pati, on a monthly, weekly and daily scale. Organizing needs to be clear about the division of work and duties of each member involved. The implementation of the SKCK Keliling service is expected not only at the Joyo Kusumo Stadium but to move to other places such as to the other district in Pati Regency. The administrative and inherent form of supervision is carried out by making a Report on the Implementation Results and the presence of a Controlling Officer. From the 6M management element, there are still deficiencies in the implementation of SKCK Mobile activities, namely in terms of infrastructure (finger print machine) and activity budget (program budget). Key Words: SKCK Keliling, Sat Intelkam Polres Pati, Public Services